2021
DOI: 10.1097/ccm.0000000000005033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bivalirudin Versus Heparin for Maintenance Systemic Anticoagulation During Adult and Pediatric Extracorporeal Membrane Oxygenation

Abstract: OBJECTIVES: To provide a comparative analysis of conventional heparin-versus bivalirudin-based systemic anticoagulation in adult and pediatric patients supported on extracorporeal membrane oxygenation. DESIGN: Retrospective chart review study of adult and pediatric patients receiving extracorporeal membrane oxygenation from January 1, 2014, to October 1, 2019. SETTING: A large, high-volume tertiary referral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(135 citation statements)
references
References 36 publications
2
124
0
Order By: Relevance
“…No articles on the subject were found in CNKI. After screening and evaluation, ten articles [12][13][14][15][16][17][18][19][20][21] were finally included for qualitative synthesis, and nine articles [12][13][14][15][16][17][19][20][21] were included in the meta-analysis because one reference [18] met the inclusion criteria but the data of outcome presented could not be pooled in a meta-analysis. The literature retrieval and screening processes are shown in Fig.…”
Section: Literature Retrieval Results and Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…No articles on the subject were found in CNKI. After screening and evaluation, ten articles [12][13][14][15][16][17][18][19][20][21] were finally included for qualitative synthesis, and nine articles [12][13][14][15][16][17][19][20][21] were included in the meta-analysis because one reference [18] met the inclusion criteria but the data of outcome presented could not be pooled in a meta-analysis. The literature retrieval and screening processes are shown in Fig.…”
Section: Literature Retrieval Results and Study Characteristicsmentioning
confidence: 99%
“…There was only one study that reported adjusted data based on age, cannulation approach (aortic vs peripheral), ECMO type, and year of ECMO [12]. Others reported unadjusted ORs.…”
Section: Literature Retrieval Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations